Kearifan Lokal dan Penerapannya di Sekolah - Marthen Rummar (CV. Syntax Corporation Indonesia, 2022)
Local wisdom describes how to behave and act to respond to changes that are unique in the physical and cultural environment of the local area. The local potential in each region in Indonesia is an asset of natural, human, technological, and cultural resources that must be maintained and developed to improve a more civilized life. In general, school learning has been paying less attention to this local aspect, so that the younger generation slowly starts to leave the noble values of the local area. The purpose of this article is to outline the form of instilling local wisdom through education or school.